Measuring Capital Stocks and Capital Services in Switzerland - Barbara Rudolf; Mathias Zurlinden (Swiss Journal of Economics and Statistics, 2009)
This paper presents estimates of the aggregate net (welath) capital stock and of aggregate capital services for Switzerland. We derive these estimates in a consistent way using the perpetual inventory method. Due to changes in data availability, the time series cover the period 1970-2005 for the 2-asset breakdown (equipment and structures) and 1990-2005 for the 12-asset breakdown (nine categories of equipment and three of structures). The sensitivity of the results is examined by varying the assumptions on the initial capital stocks, the length of asset lives, the method to calculate service prices, and the choice of ICT deflators.
Keywords: C43; D24; D92; E22; 330; capital stock; capital services; ICT goods